Gambling business as one of the main activities of organized criminal groups - Топорецька , З. М. (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2017)
The article deals with the features of committing illegal gambling by organized criminal groups. It is defined the structure and features of composition of organized criminal groups (OCG), that are created to commit illegal gambling. The authors have identified factors, which contribute to the complexity of investigation of this crime and suggested ways to improve its investigation. Оrganized criminal groups, which is created to commit therein gambling usually are: the owner of gambling – Head OCG; a person who is a personal assistant to the owner of gambling and on behalf provides instructions and forms the group; the person who conducts official and unofficial accounts, submit reports and manages all financial matters – «CFO»; persons who are nominee directors of companies partners who lease gaming equipment, facilities for gambling, etc., but do not carry out gambling. To increase the efficiency of detection and investigation of gambling that committed by OCG, Ukraine should take a number of measures, including: eliminate corruption in law enforcement; develop guidelines to investigate gambling, committed by OCG; establish active cooperation of law enforcement bodies with the media and the public to formation of public negative attitude to gambling; legalize and strictly regulate gambling by allowing only some of the casino gambling and by prohibiting games on slot machines and sports betting. Establish criminal responsibility for the organization and conduct of prohibited gambling. Create a single electronic system of adoption rates with the possibility of continuous control of public authorities. Create a single register of gaming equipment and mandatory labelling of each of its units (assigning a unique code) and equipping gaming equipment with GPS navigation.

У статті розглянуто особливості вчинення зайняття гральним бізнесом організованими злочинними угрупуваннями, визначено структуру та особливості суб’єктного складу організованих злочинних груп, які створюються для вчинення зайняття гральним бізнесом. Автором визначено чинники, які впливають на складність розкриття та розслідування цього злочину, у випадку його вчинення організованими злочинними угрупуваннями, а також запропоновано шляхи підвищення ефективності його розслідування.
ГРАЛЬНИЙ БІЗНЕС ЯК ОДИН З ОСНОВНИХ ВИДІВ ДІЯЛЬНОСТІ ОРГАНІЗОВАНИХ ЗЛОЧИННИХ УГРУПУВАНЬ
Keywords: gambling; gambling; organized criminal groups; investigation; criminal procedure.; гральний бізнес; азартні ігри; організована злочинність; розслідування; кримінальний процес.